The Future of Public Administration: Adapting to New Challenges and Opportunities in the 21st Century - Irwan Suryadi (Penelitian dan Pengembangan Ilmu, 2024)
The future of public administration in the 21st century is closely linked to the changes and opportunities brought by technological advances, changing societal needs, and global trends. This research highlights the important role of technological innovation in improving the quality of public services, with a focus on efficiency and effectiveness. Through a systematic approach of literature review, this study aims to identify effective technological innovations in the context of public administration and evaluate their impact on service performance. Research methods involve searching and analyzing data from major academic databases, scientific journals, and government reports. The findings show various types of technological innovations being used, including e-government, big data analysis, artificial intelligence, Internet of Things, blockchain, and virtual reality. The implications of this research emphasize the importance of integrating technology with policy and organizational structure to increase the effectiveness of public services.